Immune Microenvironment and Genetics in Malignant Pleural Mesothelioma - Wadowski, Benjamin; Bueno, Raphael; De Rienzo, Assunta (Frontiers in Oncology, 2021)
Malignant pleural mesothelioma (MPM) is a rare and aggressive malignancy with limited therapeutic options beyond surgery and cytotoxic chemotherapy. The success of immune checkpoint inhibition has been found to correlate with expression of immune-related genes such as CD274 (PD-L1) in lung and other solid cancers. However, only a small subset of MPM patients respond to checkpoint inhibition, and this response has been varied and unpredictable across several clinical trials. Recent advances in next-generation sequencing (NGS) technology have improved our understanding of the molecular features of MPM, also with respect to its genetic signature and how this impacts the immune microenvironment. This article will review current evidence surrounding the interplay between MPM genetics, including epigenetics and transcriptomics, and the immune response.